Noise sources identification in machines and mechanical devices - CEMPEL, Czesław; KOSIEL, Urszula (Archives of Acoustics, 1976)
This paper presents a method for the determination of noise sources locations in machines and mechanical devices. It also describes a method for the determination of the nature of these noise sources and their effect on the overall noise. The former is based on the properties of the frequency band correlation function, the latter on the properties of the coherence function. It is shown that these two methods can be used in attempts to minimize machine noise.